METODE BUDIDAYA TAUGE DALAM SMART GREEN HOUSE DENGAN SISTEM PENYIRAMAN OTOMATIS - Kevin Arie Sandy; Arnold Aribowo; Alfa Satya Putra; Aditya Rama Mitra (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2021)
There are many techniques to cultivate mung bean sprout, however the process requires many human involvements which can cause problems, such as forgetting to water the mung bean sprout, cutting the tail which must be cut one by one, finding the ideal location, and detecting water leakage. In this research, mung bean sprout will be grown with an automatic watering system in a Smart Green House system, which is able to monitor the mung bean sprout using technologies such as light, temperature and humidity sensors to determine the ideal place of cultivation, water level sensor to measure remaining water level in the container, and water sensor to detect water leakage from the planting medium. Arduino Mega 2560 is used as the microcontroller in this system. The sensors and components used in the system includes Light Dependent Resistor GL5506, Water Sensor Funduino, buzzer, Ultrasonic Ping HC-SR04, Humidity and Temperature Sensor DHT11, potentiometer, servo motor, relay with 12V pump, Knee and Nipple Watering System, and Fogger Head Sprayer. The system is able to cultivate mung bean sprout with length of 3-5 cm, without losing their color in the process, and can be harvested without tail.